THE MUSICALITY OF BATANGHARI SEMBILAN: A REPRESENTATION OF SOUTH SUMATRA'S SOCIETY - Siswanto, Silo; Sunarto, Bambang; Sunarto, Budi Setiyono (Institut Seni Indonesia Padangpanjang, 2024)
Batanghari Sembilan Music is a term used to name a musical art form in one of the regions of South Sumatra. This art form consists of musical elements, including a type of poetry called